An Apoferritin-Based Drug Delivery System for Jerantinine A Acetate for Breast Cancer Treatment - Abuzaid, Haneen M. (2022)
Natural products have been a major and critically important source of anti-cancer drugs and inspiration for drug discovery. The Aspidosperma alkaloid Jerantinine A (JA) is a natural compound that possesses potent antiproliferative activity against various human-derived carcinoma cell lines. Jerantinines elicit potent but unselective effects by inhibiting tubulin polymerisation, polo-like kinase 1 (PLK1) and increasing ROS levels in treated cancer cells. Herein, we address the poor cancer-selectivity of JA acetate (JAa) and by developing an apoferritin (AFt) delivery vehicle for JAa, which can target transferrin receptor-1 (TFR1)-overexpressing breast cancer cells. The therapeutic benefits of AFt-JAa were evaluated in a panel of breast carcinoma cell lines. By optimising the pH-mediated reassembly method, a high yield was achieved with ~77% protein recovery. Following optimisation, ~120 molecules of JAa were successfully encapsulated within the AFt protein cavity. The AFt-JAa formulation has comparable size, charge and cage-integrity to AFt stock, as demonstrated by dynamic light scattering (DLS) and native polyacrylamide gel electrophoresis (PAGE). AFt- JAa was stable for ≥ 10 months of storage at T = 4 ºC and pH 7.4. Treatment of cells with AFt-JAa significantly enhanced breast cancer cell growth inhibition in cells with high TFR1 expression but not MRC-5 fibroblasts that express low TFR1 levels; TFR1 levels were detected with western blot and flow cytometry. Enhanced selectivity of encapsulated JAa in TFR1-overexpressing breast cancer cells was explained by enhanced internalisation of 5-carboxyfluorescein-conjugated-human-AFt compared to TFR1-low expressing cells (MRC-5 fibroblasts). Consequently, enhanced AFt-JAa nanoformulation potency (over naked JAa) was attributed to greater intracellular accumulation of JAa in cells overexpressing TFR1 (SKBR-3, MDA-MB-231 and BT-474). Greater stability was observed for AFt-JAa in culture media under the treatment conditions (T = 37 ºC; ≤ 72 h) compared to the naked agent. The enhanced activity of AFt-JAa was supported by a greater reduction of colony formation in TFR1+ breast carcinoma cell lines SKBR-3, MDA-MB-468 and BT-474. Significantly lower number of viable cells, more profound cell cycle perturbation, including G2/M arrest, and increased apoptosis was evoked by AFt-JAa compared to JAa alone. Significant dose-dependent upregulation of biomarkers of apoptosis (cleaved PARP, decreased PLK1 and Mcl-1/Bcl-2 expression) further corroborates apoptosis. Treatment with naked and AFt-encapsulated JAa leads to the generation of ROS in MCF-7 and MDA-MB-231 cells, in addition to upregulating expression of WT p53 in MCF-7 cells, while repressing mutant p53 expression in both SKBR-3 and MDA-MB-231. These results indicate multiple cancer-related targets of JAa and confirm the natural product’s rich and diverse pharmacology. AFt alone exerts negligible effects on cell growth or survival as indicated from MTT, cell count, clonogenic, cell cycle analysis, annexin V apoptosis assays; neither does AFt impact the expression of apoptotic/antiapoptotic proteins, as shown by western blot. Thus, AFt is a potentially biocompatible nanocarrier for targeted delivery of JAa to minimise its toxicity and enhance its activity in TFR1-overexpressing tumours.